Alluvial ridge development and structure: Case study on the Upper Tisza, Hungary - Kiss, Timea; Sipos, György; Vass, Róbert (Geographica Pannonica, 2022)
The juxtaposition of natural levees results in alluvial ridges with a unique fluvial record. Our aims were to (1) identify the alluvial ridges of the Upper Tisza (Hungary); (2) determine their morphological characteristics; and (3) reconstruct the Late Quaternary fluvial history of the region. The oldest paleo-meander was abandoned ca. 29 ka ago; referring to early avulsion of the Tisza. Five alluvial ridges were identified with intensive fluvial activity at ca. 12-13 ka, 7.7-8.6 ka, 6.1-6.6 ka, 4.8 and 2.9 ka ago. Moderate fluvial activity was indicated by early Atlantic and Subboreal paleosols. The sedimentation rate in the paleo-channels (0.3-0.5 mm/y) and on the alluvial ridges (0.3-0.5 mm/y) was slow, influenced by the reactivation of a paleo-channel.